Effect of distillation methods on qualitative characteristics of distillates obtained from dried Jerusalem artichoke - Krikunova L.; Dubinina E. (Техника и технология пищевых производств)
The given article considers the perspectives of using dried Jerusalem artichoke as an alternative raw material in distilled spirits production. The main objective of the research was to determine the effect of distillation methods of fermented wort obtained from dried Jerusalem artichoke on the distillate output and quality. The authors took dried Jerusalem artichoke instead of its fresh tubers for processing as a raw material for alcohol drinks production because it is possible to use it during for the whole year to produce beverages. Besides dried Jerusalem artichoke has stable biochemical composition, high microbiological quality, and higher content of low-molecular fractions of fermented carbohydrates. The study of physical, chemical and organoleptic properties of the fermented wort, crude alcohol and distillate was carried out using standard analytical methods. The authors considered two types of distillation: single and double. During the experiments they used dried Jerusalem artichoke with humidity 6.1% and inulin content equal 54.2%. Fermented wort was obtained by means of single-stage method. Distillation was performed using distillation unit «Kothe Destillationstechnik» (Germany). The authors determined that distillation method has an influence on the distribution of ethanol into fractions and determines its loss. Double distillation leads to higher loss of ethanol. Ethanol loss increased from 3.6% after single distillation up to 5.2% after double distillation. The authors showed that during single distillation of the fermented wort obtained from dried Jerusalem artichoke more volatile components are formed compared to double distillation. In the first case their number increases by 10.0%, in the second case – only by 3.5%. The data on the composition of volatile constituents in the distillates allowed to prove that single distillation has a number of advantages such as the production of liquids rich in valuable volatile constituents and lower methanol content which is considered as the most toxic impurity.